Asymptotic estimates of approximation of continuous periodic functions by the Fourier sums - Gavrilyuk, V. T. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
Asymptotic estimates, expressed in terms of the value of the modulus of continuity of r-th order (r≥ 2) at the point t = π/n of a function fC_2π or of the (ψ,β)-derivative of a function f C_β^ψC, are established for the deviations of continuous periodic functions from their Fourier sums.